A Study on Sustainability in the Firm Value of Banking Business: An Interaction of Financial Attributes and Risk Governance - Samyukta Jena, Kishore Kumar Das, (European Economic Letters (EEL), 2025)
Purpose Of the Study: Evolution of the business environment has forced the financial institutions to turn around and change their own business models in order to retain their loyal customer base. The commercial banks have certainly faced their own fair share of challenges when they had to introduce innovations in their products and processes and simultaneously strengthen their financial health with sustained risk governance techniques and decisions. Thus, the purpose of the study is to understand the importance of sustainability of firm value for a banking business, and how financial attributes and risk governance factors can impact the farm valuation of Indian commercial banks. A Brief Literature Review: Over the years authors have tried studying the relation between firm value and various financial attributes. In certain instances, risk governance techniques like the capital adequacy ratio have also been introduced in various studies. In a study, the author tried to study the relationship between financial risks and firm value and examine the moderating effect that capital adequacy has on the relationship between financial risk and firm value. The results of the study indicated that a higher capital adequacy ratio increases form value and has a moderating effect on financial risk and firm value (Jagirani et al., 2023). Similarly, certain authors over the years have also tried to find out the effectiveness of Risk Committee on the financial success of certain quoted banks in African countries. (Odubuasi et al., 2022) focused specifically on risk committee diligence committee composition committee diversity, committee expertise, committee size and return on equity of the country’s selected from Africa. The fixed effect model employed by them reported that the impact of the diligence and composition of risk committee on bank performance in certain African countries was highly significant. Thus, they concluded that risk committee effectiveness, its diligence, its composition and various leverage factors should be pivotal in the formulation of risk management committee of various organisations, and especially banks. The Methodology Adopted: Content analysis and panel data has been employed in the study to understand the implications of the financial attributes and risk governance factors on the sustainability in the firm value of Indian commercial banks. Financial attributes like Net Interest Margin, Cash Deposit ratio, Volume of digital transactions, etc. and risk governance attributes like the presence of a chief risk officer, the activism of the risk committee, etc. have been used in the study. Tobin’s Q has been taken as the proxy of firm value in the study as well. The hierarchical regression analysis has been the economic modelling technique used in the study to achieve the study purpose. Study Hypothesis: Since hierarchical regression modelling has been used in the study, the aim of the study is to assess whether the overall model of firm value of the banking business gets better with the gradual introduction of certain financial attributes variables and risk governance variables or not. Accordingly, with each step and introduction of certain attributes and variables into the model, research hypothesis in the study has been developed. Results & Findings: The study is an attempt at introducing a functional model with some significant financial ratios, some crucial ratios that define the characteristics of the bank and the risk governance framework with the firm value. The logic behind using the Tobin’s Q as a proxy of firm value is that unlike several other financial ratios that solely focus on the book value of the variables; the Q ratio takes the market capitalization value of the banks into account in the study. Through the study, almost all the explanatory variables like CDR, ROE, ROA etc. showed a positive and significant relationship with firm value in the first 2 models whereas on the other hand, introducing risk governance in the third model made it too complicated. As a result, the model was proven insignificant and unproductive unlike the first 2 models. Limitations: There is a lot of scope for further research on this particular subject as the model could be developed in a lot of ways to explain how different variables may it be financial ratios, risk governance or financial innovativeness rating etc. could impact the firm value which in turn impacts the managerial decision making of senior executives and the economy as a whole and further help in making the banking business is sustainable. Implications: The study gives us a glimpse of certain financial attributes and various risk governance factors that could be used to maintain and sustain the firm value of commercial banks in India. It is certainly essential to focus on the sustainability of firm value of commercial banks, for the reason that banks are the lifeblood of an economy and help act as the mediating factor between deposits, savings and investment in the economy.